2020
DOI: 10.24251/hicss.2020.288
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media during Social Movements – Observations from the #metoo Debate on Twitter

Abstract: In recent years, the development of information communication technologies (ICT) such as social media changed the way people communicate and engage in social movements. While conventional movements were fought in the streets, social media enabled movements to take place online. In this paper, we aim to investigate the role of social media during social movements which evolve online. Specifically, we examined Twitter communication during the #metoo debate. To this end, we applied methods from social network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…These examples show that hashtags cannot only promote public attention but also help to connect individual members of movements and enable them to act collectively. Altogether, the above-described strategies provide a strong counterargument to the accusation of online activism being pure "slacktivism," which suggests that although online participation is easy to perform through a simple click, actual identification with the particular movement might still be low (Brünker et al, 2020). The question underlying this article is, therefore, how SMOs adjust to an online-only environment and use hashtag activism to facilitate collective action.…”
Section: Social Media and Smosmentioning
confidence: 96%
“…These examples show that hashtags cannot only promote public attention but also help to connect individual members of movements and enable them to act collectively. Altogether, the above-described strategies provide a strong counterargument to the accusation of online activism being pure "slacktivism," which suggests that although online participation is easy to perform through a simple click, actual identification with the particular movement might still be low (Brünker et al, 2020). The question underlying this article is, therefore, how SMOs adjust to an online-only environment and use hashtag activism to facilitate collective action.…”
Section: Social Media and Smosmentioning
confidence: 96%
“…Comparing the first 200 power users with the following 100 power users in the retweet ranking, our results reveal that Private Persons were particularly active in the lower retweet rankings of power users [14]. This suggests that Private Persons might not be that popular in getting retweeted compared to, for example, Celebrities.…”
Section: Dynamics Of Roles Participating In Social Movements On Twittermentioning
confidence: 81%
“…However, these pieces have so far not been put together. Less is known about the influence on the retweet probability of specific content that is shared by specific user groups [14]. Yet, to broaden the understanding of social movements on social media, it is crucial to understand the dynamics of communication among distinct groups participating in a social movement on social media [36].…”
Section: Introductionmentioning
confidence: 99%
“…Lundgaard et al [7] manually classified 2,050 tweets regarding the #BlackLivesMatter movement into five categories (raising awareness, offline activism, anti-authorities, victimization, and collaboration). Similarly, through manual content analysis, Brünker et al [16] found sharing of personal information, reference, call for action, and testimony to be the main content categories in a sample of 1,271 tweets related to the #metoo movement. In their study of 6,874 tweets posted by six traumatic brain injury patients, Brunner et al [17] handcoded the tweets into six categories: supporting others, society and culture, connecting with others, life after the illness, knowledge, and advocacy.…”
Section: Related Workmentioning
confidence: 99%